Performance records of autochthonous goats in Central Serbia - Maksimović Nevena; Ružić-Muslić Dragana; Caro-Petrović Violeta; Pantelić Vlada; Cekić Bogdan; Ćosić Ivan; Lazarević Marina (Biotechnology in Animal Husbandry, 2019)
The purpose of this study was to determine status, number and present level of productivity of autochthonous goats raised in Central Serbia on smallholder farms. Study included quality breeding animals of Balkan and Serbian white goat breed registered in Central herd book. Productivity data were collected from regular annual performance recordings at 11 smallholder farms for 145 Balkan does (2-9 years of age) and 203 kids and 83 Serbian white does (2-10 years of age) and 109 kids. Traits recorded were as follows: body weight of does, body weight of kids at birth, at the age of 30 days and at weaning, prolificacy of does and milk production. The analysis showed the average body weight of does to be 43.07 kg for Balkan does and 47.42 kg for Serbian white does. Average body weight of kids at birth, 30 days of age and weaning was 2.22 kg, 6.87 kg and 15.71 kg, respectively for Balkan breed and 3.66 kg, 7.24 kg and 14.23 kg for Serbian white breed. Prolificacy was 140% in Balkan and 131% in Serbian white does. Among dairy production traits, following results were obtained for Balkan and Serbian white goat respectively: lactation length 199 and 229 days, total milk yield 257.89 kg and 459.49 kg, milk fat content 4.03% and 3.79%, milk protein content 3.06% and 3.35%. Number of quality breeding animals registered at Central herd book in 2018, as presented in Institute for Animal Husbandry's annual report for goats for Central Serbia in 2018, was 159 for Balkan and 138 for Serbian white goat. As these breeds represent a valuable and irreplaceable source of genetic variability, as well as very important cultural and traditional heritage and further emphasis should be on preserving and increasing their number.